Quantification of total polyphenol content in wine lees by conventional optical and photoacoustic spectroscopy - Ottó Dóka; Gitta Ficzek; Gergely Simon; Zsolt Zsófi; Szabolcs Villangó; György Végvári (OENO One, 2023)
The He-Ne laser (632.8 nm) and photoacoustic spectroscopy (PAS), a variant of the photothermal methods, were combined with the Folin-Ciocalteu colorimetry method to determine total phenolics in wine lees. Utilising this method we found that the total polyphenol content of the nine selected wine lees varied from 1305 to 3907 mg/L. The gallic acid equivalent was determined by means of spectrophotometry using 765 nm as the analytical wavelength. The original Folin-Ciocalteu colorimetry assay was modified for the PAS measurements. Since the PAS does not need dilution, the filtration steps and the Folin-Ciocalteu reagent were used directly on the wine lees samples. Using the original colour reaction process and the modified reaction, the PAS showed linear behaviour between the total polyphenol content and the PA signal; the results of which gave determination coefficients of 0.9946 and 0.9936, while the limit of detection was 232.6 mg/L in both cases.